INASP support to improve medical journals of developing countries: BJMS experience (Bangladesh Journal of Medical Science, 2012)
DOI: http://dx.doi.org/10.3329/bjms.v11i2.11417 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012 71-73